Indonesia’s 2023 ASEAN Chairmanship: Challenges and Policies Taken - Jonathan Siborutorop (UIN Syarif Hidayatullah Jakarta, 2024)
Abstract. As Indonesia has recently completed its term in the chair position for 2023, a study is needed to determine the link between ASEAN's policy goals, agendas, and their outcomes as reflected by common communiques during Indonesia's chairmanship and Indonesian national policies and interests. Using a qualitative descriptive method, this study will examine two questions: firstly, how is Indonesia’s ASEAN chairmanship in 2023 influenced by its pre-existing national foreign policy doctrine, and secondly, how is it reflected in its policy outcomes as chairman of ASEAN? This study examines these questions in the lifht of the three main issues that ASEAN faced during Indonesia’s chairmanship in 2023: the conflict in Myanmar, the ASEAN bloc’s relations with China, Russia, and the US, particularly in the context of the South China Sea dispute and the war in Ukraine, and regional integration and inter-country connectivity within ASEAN. Finally, this study will examine how Indonesia has successfully utilized its ASEAN chairmanship to achieve its internal policies and amplify them to the regional and global stage.Keywords: ASEAN, Foreign Policy, Regional Integration, South China Sea, Indonesia, national interests.Abstrak. Mengingat Indonesia baru saja menyelesaikan masa jabatannya sebagai negara ketua ASEAN pada tahun 2023, diperlukan sebuah kajian untuk mengetahui kaitan antara tujuan kebijakan, agenda, dan hasil kebijakan ASEAN, sebagaimana tercermin dalam berbagai keputusan bersama yang dilakukan pada masa kepemimpinan Indonesia, dengan kebijakan dan kepentingan nasional Indonesia. Dengan menggunakan metode deskriptif kualitatif, penelitian ini akan mengkaji dua pertanyaan: pertama, bagaimana kepemimpinan Indonesia di ASEAN pada tahun 2023 dipengaruhi oleh doktrin kebijakan luar negeri nasional Indonesia yang sudah ada sebelumnya, dan kedua, bagaimana pengaruh tersebut tercermin dalam hasil kebijakan Indonesia sebagai ketua ASEAN? Kajian ini menguji pertanyaan-pertanyaan tersebut dalam lensa tiga permasalahan utama yang dihadapi ASEAN pada masa kepemimpinan Indonesia pada tahun 2023: konflik di Myanmar, hubungan blok ASEAN dengan Tiongkok, Rusia, dan Amerika Serikat, khususnya dalam konteks sengketa Laut Cina Selatan dan perang di Ukraina, dan integrasi dan konektivitas regional antarnegara ASEAN. Terakhir, studi ini akan mengkaji bagaimana Indonesia berhasil memanfaatkan masa kepemimpinannya di ASEAN untuk mensukseskan kebijakan internalnya dan menyuarakan kebijakan tersebut di tingkat regional dan global.Kata Kunci: ASEAN, politik luar negeri, integrasi regional, Laut Cina Selatan, Indonesia, kepentingan nasional.